Where cultures and languages meet – the language of nineteenth-century Belarus in the literary representation of Jan Barszczewski - Kuryłowicz, Beata (Papers in Linguistics, 2025)
Jan Barszczewski is a little-known, yet extremely talented writer of early Romanticism who came from the Northeastern Borderlands of Poland. Thoroughly educated, well versed in Latin and Greek, familiar with the latest currents of world literature, he consciously drew on folklore as well as cultural, historical and linguistic elements from the Połock region, which he particularly cherished as the land of his childhood. The aim of the article is to present dialect stylization in the work Szlachcic Zawalnia czyli Białoruś w fantastycznych opowiadaniach, considered one of the peak achievements of Polish Romantic prose. Creating at the junction of two cultures and two languages, with aesthetic detachment Barszczewski employed Belarusian folklore, which he treated as the creative material of his works. The undertaken analysis of the linguistic material shows that the writer, describing events from folk culture, deliberately introduced into his work linguistic means typical of the regional, dialect variety, so that the language of his characters would be congruous with other elements of the depicted world. Barszczewski selected and wove into the text of the work the most expressive elements of the language of the 19th-century Borderlands.